NON-DIGITAL LANGUAGE GAMES TO CREATE MEANINGFUL LEARNING EXPERIENCE FOR ADULT LEARNERS - Sastrikirana, Anastasia; Pramudita, Wahyu (Journal of English Educational Study (JEES), 2024)
Civil servants are expected to be professional and competent because they have to be able to work well and to tackle challenges in VUCA conditions. To improve their competitiveness, opportunities to continue to higher level of education are given. Those who take these opportunities should attend TOEFL Preparation classes held by the Language Training Center of the National Institute of Public Administration. In order to help them learn TOEFL, three non-digital language games were developed and applied in the classroom to help them learn. To obtain data whether these games could create meaningful learning this research was conducted. Data were gathered from online questionnaire whose questions were revolved around five attributes of meaningful learning and also from classroom observation. The results showed that all attributes of meaningful learning which were active, constructive, intentional, authentic, and cooperative were achieved. The games enabled them to actively and enthusiastically played the non-digital language games with their classmates. They also shared common knowledge that they could use to answer Structure and Written Expressions questions. They also mentioned that the games helped them construct their initial knowledge and the new knowledge they learnt in the classroom. They also agreed that the games enabled them to obtain a clear description of the real TOEFL Structure and Written Expressions.Keywords: non-digital language games; meaningful learning experience; adult learners